The effect of resistance exercise priming in the morning on afternoon sprint cross-country skiing performance - Rud, B.; Øygard, E.; Dahl, E. B.; Paulsen, G.; Losnegard, T. (International Journal of Sports Physiology and Performance, 2021)
Purpose: We tested whether a single session of heavy-load resistance priming conducted in the morning improved double-poling (DP) performance in the afternoon.